2014
DOI: 10.1186/1471-2164-15-183
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of gene expression of Paramecium bursaria with and without Chlorella variabilissymbionts

Abstract: BackgroundThe ciliate Paramecium bursaria harbors several hundred cells of the green-alga Chlorella sp. in their cytoplasm. Irrespective of the mutual relation between P. bursaria and the symbiotic algae, both cells retain the ability to grow without the partner. They can easily reestablish endosymbiosis when put in contact with each other. Consequently, P. bursaria is an excellent model for studying cell–cell interaction and the evolution of eukaryotic cells through secondary endosymbiosis between different p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
81
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(83 citation statements)
references
References 42 publications
1
81
1
Order By: Relevance
“…2A-B). The influence of symbionts in host gene expression has been shown in other symbiotic associations (Lehnert et al 2012, 2014, Kodama et al 2014, Zhao et al 2014). Comparative transcriptional analysis performed in orchid Cymbidium hybridum in the presence or absence of the mycorrhizal fungus showed that the symbiont positively influences plant gene expression.…”
Section: Resultsmentioning
confidence: 86%
“…2A-B). The influence of symbionts in host gene expression has been shown in other symbiotic associations (Lehnert et al 2012, 2014, Kodama et al 2014, Zhao et al 2014). Comparative transcriptional analysis performed in orchid Cymbidium hybridum in the presence or absence of the mycorrhizal fungus showed that the symbiont positively influences plant gene expression.…”
Section: Resultsmentioning
confidence: 86%
“…Likely, the underlying molecular mechanism involves an increase of Paramecium heat-shock gene ( hsp ) expression caused by the symbiont (Hori and Fujishima, 2003). Enhanced hsp mRNA levels have also been observed for Paramecium bursaria living in symbiosis with the photosynthetic microalgae Chlorella (Kodama et al, 2014). If H. caryophila likewise effects the hsp expression of its host has not yet been studied.…”
Section: Discussionmentioning
confidence: 89%
“…Chlorovirus hosts, which are normally endosymbionts, are often referred to as zoochlorellae (Karakashian & Karakashian, 1965; Karakashian, 1975; Kodama et al, 2014). They are associated with either the protozoan Paramecium bursaria , the coelenterate Hydra viridis or the heliozoon Acanthocystis turfacea (Van Etten & Dunigan, 2012).…”
Section: Introductionmentioning
confidence: 99%